Diversity and Distribution of Boletoid Fleshy Pored Fungi in Uttarakhand Himalaya, India (2007–2023): A Comprehensive Study - Semwal, Kamal C; Bhatt, Vinod K; Dhyani, Anurag (Acta Biologica Szegediensis, 2025)
This study provides a comprehensive analysis of boletoid fleshy pored fungi across the elevational zones of Uttarakhand Himalaya, India, from 2007 to 2023. The study encompasses 167 collections representing 24 genera and 46 species, including lamellate members. Key genera include Aureoboletus, Austroboletus, Boletellus, Boletus, Borofutus, Cyanoboletus, Gyrodon, Gyroporus, Hemileccinum, Hortiboletus, Indoporus, Lanmaoa, lamellate boletoid members, Leccinellum, Leccinum, Phylloporus, Porphyrellus, Pulveroboletus, Rugiboletus, Strobilomyces, Suillus, Sutorius, Tylopilus, Xerocomellus, and Xerocomus. The paper includes field photographs, staining reactions on bruising of pores and sliced context, spore prints, microscopic images, and commentary on species determination, aiding readers in understanding the rich species diversity of boletoid mushrooms in Uttarakhand Himalaya. The compiled information serves as a baseline for aspiring researchers, guiding them to explore new localities for novel species of boletoid fleshy pored fungi. Recommendations for future research include extensive fungal forays, classical taxonomy, and advanced molecular studies, given the widespread occurrence of these mushrooms across before the Uttarakhand Himalaya's forest types.